Contribution of a KCNH2 variant in genotyped long QT syndrome: Romano–Ward syndrome under double mutations and acquired long QT syndrome under heterozygote. Issue 1 (July 2017) - Fujii, Yusuke; Matsumoto, Yuichi; Hayashi, Kenshi; Ding, Wei-Guang; Tomita, Yukinori; Fukumoto, Daisuke; Wada, Yuko; Ichikawa, Mari; Sonoda, Keiko; Ozawa, Junichi; Makiyama, Takeru; Ohno, Seiko; et al.
Abstract: Background: Long QT syndrome (LQTS) presents two clinical phenotypes, congenital and acquired forms. This study aims to evaluate the genetic contribution of a KCNH2 variant for the two LQTS phenotypes. Methods: From 1996 to 2014, genetic screening for LQTS probands was performed for five major genes: KCNQ1, KCNH2, SCN5A, KCNE1, and KCNE2 and 389 probands were found to be mutation carriers. We analyzed the clinical phenotypes of p.His492Tyr carriers in KCNH2 . Results: Heterozygous p.His492Tyr variant was identified in 10 LQTS families. Six probands (mean age, 26 ± 23 years) carried another mutation, and two of six had syncope associated with emotional stress or telephone ringing. The remaining four probands were significantly older at diagnosis (mean age, 42 ± 33 years) and carried no other compound mutations. All the four probands had fatal arrhythmic events in the presence of additional precipitating factors such as culprit drugs in 2, hypokalemia in 1, and bradycardia in 1. The QTc interval of carriers with p.His492Tyr alone was 445 ± 10 ms and significantly shorter than that in double mutation carriers (481 ± 40 ms, p = 0.041). Conclusions: KCNH2 p.His492Tyr variant presented Romano–Ward syndrome in the presence of another mutation and heterozygous carriers had mild phenotypes while even heterozygous carriers should be cared for not to encounter secondary factors because incidental factors could manifest "latent" form of p.His492Tyr heterozygous carriers.